Cryogenics Course - Zergane Said (University of M'sila, 2024)
This course manuscript serves as an educational resource for the cryogenics module aimed at third year undergraduate students in the LMD program, energy option. Designed in line with the official curriculum, it aims to deepen understanding of cryogenics by utilizing knowledge of thermodynamics, heat transfer, and extremely low temperatures. It covers the main applications of the field as well as common techniques for producin g cryogenic fluids, both for everyday uses and industrial needs. The document also examines thermodynamic cycles used in low temperature production, natural gas liquefaction processes, and the production of liquid compounds from air. Each chapter concludes with practical examples and solved exercises, making it easier to assimilate the concepts. Presented as detailed lectures and illustrated with concrete examples, this manuscript facilitates a clear and progressive understanding of cryogenics.
Course Handout intended for students of the Bachelor's Degree in Energy Engineering
Keywords: Cry ogenics; Joule Thomson expansion; cryogenic cycles; gas liquefaction; low temperature; gas separation.